Captura de conocimiento a través de modelamiento - Bolaños Castro, Sandro Javier (Ingeniería, 2003)
This paper makes reflexive review , about drive of knowledge and propose a way to capture it throughdifferent conceptual models, using graph theory fundamentals and the definition that the article do how intentional semantic graph.